The wrath of the gods : masterpieces by Rubens, Michelangelo, and Titian - Atkins, Christopher D. M. (Philadelphia Museum of Art, 2015)
Peter Paul Rubens (1577-1640) proudly described his monumental painting Prometheus Bound as first among "the flower of my stock." This singular work demonstrates how Rubens engaged with and responded to his predecessors Michelangelo and Titian, with whom he shared an interest in depictions of physical torment. This book offers an in-depth case study of the Flemish artist's creative process and aesthetic, while also demonstrating why this particular painting has appealed to viewers over time. Many scholars have elaborated on Rubens's affinity for Titian, but his connection to Michelangelo has received far less attention. This study presents a new interpretation of Prometheus Bound, showing how Rubens created parallels between the pagan hero Prometheus and Michelangelo's Risen Christ from the Sistine Chapel's Last Judgment. Christopher D.M. Atkins expands our understanding of artistic transmission by elucidating how Rubens synthesized the works he saw in Italy, Spain, and his native Antwerp, and how Prometheus Bound in turn influenced Dutch, Flemish, and Italian artists. Exhibition: Philadelphia Museum of Art, USA (12.9.-6.12.2015)